The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1021/acsami.6b00663
|View full text |Cite
|
Sign up to set email alerts
|

Vertically Aligned Nitrogen-Doped Carbon Nanotube Carpet Electrodes: Highly Sensitive Interfaces for the Analysis of Serum from Patients with Inflammatory Bowel Disease

Abstract: The number of patients suffering from inflammatory bowel disease (IBD) is increasing worldwide. The development of noninvasive tests that are rapid, sensitive, specific, and simple would allow preventing patient discomfort, delay in diagnosis, and the follow-up of the status of the disease. Herein, we show the interest of vertically aligned nitrogen-doped carbon nanotube (VA-NCNT) electrodes for the required sensitive electrochemical detection of lysozyme in serum, a protein that is up-regulated in IBD. To ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 51 publications
(87 reference statements)
1
20
0
Order By: Relevance
“…Among others, recent approaches based on nanomaterials, such as graphene [105] or nanoceria [106], show promising potentialities; (iv) Validation of novel aptasensors in comparison with methods currently used in clinical and analytical laboratories, such as ELISA and HPLC. So far, only three studies reported comparative results obtained with the aptasensor and by classical methods [73,78,91]. In the particular case of lysozyme, a comparison with other methods should be made with caution, since some methods measure the amount of enzymatically-active lysozyme, while others determine the total amount of protein.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Among others, recent approaches based on nanomaterials, such as graphene [105] or nanoceria [106], show promising potentialities; (iv) Validation of novel aptasensors in comparison with methods currently used in clinical and analytical laboratories, such as ELISA and HPLC. So far, only three studies reported comparative results obtained with the aptasensor and by classical methods [73,78,91]. In the particular case of lysozyme, a comparison with other methods should be made with caution, since some methods measure the amount of enzymatically-active lysozyme, while others determine the total amount of protein.…”
Section: Discussionmentioning
confidence: 99%
“…Recent developments in biosensing research illustrate the applications of aptasensors for the dual detection of lysozyme and other important analytes, such as adenosine [95], thrombin [89,94] and interferon gamma [90]. The usefulness of aptasensors for serum analysis of patients with inflammatory bowel disease was recently demonstrated [73]. Consequently, new studies focused on the parallel analysis and correlations between disease biomarkers and lysozyme levels in biological samples are expected to boost research efforts tapping into the applicative potential of electrochemical aptasensing of lysozyme in the biomedical field.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For improved performance, controlled deposition of CNTs was pursued by growing the CNTs on electrode surface and vertical alignment in CNTs nanocarpets. Doping of CNTs was further reported to enhance the analytical characteristics of obtained electrochemical aptasensors . The synthesis, properties and applications of carbon nanotubes in electrochemical sensing have been detailed in several reviews .…”
Section: Carbon Nanomaterialsmentioning
confidence: 99%